2005
DOI: 10.1158/1078-0432.ccr-05-0771
|View full text |Cite
|
Sign up to set email alerts
|

Basic Fibroblast Growth Factor (FGF-2) Overexpression Is a Risk Factor for Esophageal Cancer Recurrence and Reduced Survival, which Is Ameliorated by Coexpression of the FGF-2 Antisense Gene

Abstract: Purpose:The basic fibroblast growth factor (FGF-2) gene is bidirectionally transcribed to generate overlapping sense and antisense (FGF-AS) mRNAs. FGF-AS has been implicated in the posttranscriptional regulation of FGF-2 expression. The aim of this study was to characterize FGF-2 and FGF-AS in esophageal cancer and to correlate their expression with clinicopathologic findings and outcome. Experimental Design: Reverse transcription-PCR was used to study FGF-2 and FGF-AS mRNA expression (normalized to glyceralde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 56 publications
5
58
0
2
Order By: Relevance
“…First, no FGF-2 protein could be detected in CF 1-derived fibroblasts or in CF 1 fibroblast-conditioned media, although CF 1 fibroblasts expressed FGF-2 mRNA. This could be explained by the presence of antisense FGF mRNAs, which have been implicated in the posttranscriptional regulation of FGF-2 expression (Barclay et al, 2005). These antisense mRNAs could be over-expressed in CF 1-derived fibroblasts (our unpublished data).…”
Section: Discussionmentioning
confidence: 80%
“…First, no FGF-2 protein could be detected in CF 1-derived fibroblasts or in CF 1 fibroblast-conditioned media, although CF 1 fibroblasts expressed FGF-2 mRNA. This could be explained by the presence of antisense FGF mRNAs, which have been implicated in the posttranscriptional regulation of FGF-2 expression (Barclay et al, 2005). These antisense mRNAs could be over-expressed in CF 1-derived fibroblasts (our unpublished data).…”
Section: Discussionmentioning
confidence: 80%
“…14 It has been demonstrated that FGF2 has prognostic value in several malignancies, including esophageal cancer, renal cell carcinoma, ovarian cancer, lung cancer, and uterine endometrial cancer. [15][16][17][18][19][20] The down-regulation of FGF2 messenger RNA expression may be associated with increased severity of CC. 21 FGF2 can be released from both tumor cells and stromal cells.…”
mentioning
confidence: 99%
“…FGF18, a specific ligand for FGFR3IIIc, is also upregulated in colorectal cancer (Shimokawa et al 2003), suggesting that FGFR3IIIc imparts changes such as cell proliferation and migration by mediating the effects of FGF18 effects in colorectal cancer (Sonvilla et al 2010). In EC, a previous study demonstrated that the expression of FGF2, a specific ligand for FGFR3IIIc, is upregulated in the patients with poor prognosis (Barclay et al 2005). …”
Section: Research-article2015mentioning
confidence: 99%